Literasi Digital Bagi Keluarga Milenial Dalam Mendidik Anak Di Era Digital - Rini Indriani, M. Yemmardotillah (Pusdikra Publishing, 2021)
The development of technological advances in the digital era brings very significant changes in all aspects of life. In this digital era, educational problems become very diverse with the increasing family responsibilities. To deal with these developments, the expertise of parents and educators is needed to implement the right solutions to all these problems and also the ability to adapt to environmental changes. This study examines in depth digital literacy for millennial families in educating children in the digital era. Digital literacy skills are needed by teachers and parents in educating children so that they can play various roles as educators in this digital era. This research uses library research method. Data collection in this study was carried out by elaborating various kinds of literature in the form of books, journals, e-books and literature relevant to digital literacy problems in millennial families in the digital era. The data analysis technique uses content analysis methods from journals and other documents that are accessed via the internet. The results show that in this digital era the role of parents is needed so as not to be left behind. In this era, there is a need for a new reorientation of learning because it is considered to affect vision, responsibility, social sensitivity and logical ability, as well as honesty. All of this leads to a reorientation of the new role of parents, namely as agents of change, knowledge renewal, and learning consultants that emphasize creativity, initiative, good communication and cooperation between parents, schools and communities.